(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
We have considered approaches to define the concept "inclusive education". We have defined features of the communication between elder school children in the inclusive environment. Found that communication and perception of children with special needs depend much on disability form because kids with physical disabilities can more easy socialize, they are perceived better in the peer community, they are more communicated and interacted. It is proved that children’s attitude to classmates with disabilities depends on attitude of their parents to the inclusiveness and inclusive environment. We have defined, that for successful introducing inclusive education and creating a comfortable environment for all we have to work directly with parents so that they understand that introducing an inclusive environment will not harm their children, but will form their tolerance skills for children with disabilities. Therefore, it is necessary to provide parents with an understanding of the features of children with disabilities, through lectures, trainings, and viewing films about inclusive education. Further directions for exploring effective ways of presenting information on inclusive education for children and parents are perspective, which will help to eliminate stereotypes and establish active communication in an inclusive environment.